ANALYSIS OF Deoxyribonucleic Acid (DNA) FRAGMENTATION AND ACROSOME INTEGRITY AS BIOMARKERS OF FROZEN SEMEN QUALITY OF BULLS AT THE SPERM BANK OF SAMARINDA CITY - Kirana Dara Dinanti Adiputra; Novemia Fatmarischa; Dani Nur Arifin; Fikri Ardhani; Kumbawan Wibisono; Novi Ramadhani; Erni Damayanti (BRIN - Badan Riset dan Inovasi Nasional, 2026)
This study aims to evaluate the quality of frozen bull semen at the Sperm Bank of Samarinda City based on parameters of motility, viability, morphological normality, plasma membrane integrity (PMI), acrosome integrity, and DNA fragmentation, as well as their effects on cattle breeds and storage duration. The samples consisted of frozen semen from five breeds (Limousin, Madura, Angus, Simmental, and Peranakan Ongole) with different storage periods (3, 4, and 5 years). Motility, viability, and morphological normality were tested according to the Indonesian National Standards (SNI). The PMI was assessed using the hypo-osmotic swelling test (HOST), acrosome integrity using peanut agglutinin (PNA) staining, and DNA fragmentation using acridine orange (AO) staining. Data were analyzed using two-way ANOVA, and if there was an effect, it was followed by a Tukey post hoc test. The findings indicated that motility and PMI remained relatively stable; however, the duration of storage significantly influenced PMI (P<0.05). The breed of bull and storage duration had a significant effect on morphological normality, viability, acrosome integrity, and DNA fragmentation (P<0.05). However, the two factors did not interact with each other. It can be concluded that the storage duration resulted in a decline in semen quality, specifically in terms of membrane and DNA integrity. Therefore, it is recommended to use semen straws ≤ 4 years old and conduct periodic quality re-qualification to maintain frozen semen fertility.